Validation of app and phone versions of the Control of Allergic Rhinitis and Asthma Test (CARAT) - Jácome, C. (2021)
Assessment of asthma control at every opportunity is recommended. Control of Allergic Rhinitis and Asthma Test (CARAT) is a patient reported outcome measure commonly used to assess asthma control in clinical practice.It includes ten questions answered in a 4 point Like rt scale that address upper and lower airway symptoms, sleep interference, limitation of activities , and the need to increase medication over a 4 week period. CARAT is frequently administered on paper during medical visits, but digital versions through website and mobile apps are available.